2003
DOI: 10.1142/s1609945103000418
|View full text |Cite
|
Sign up to set email alerts
|

Significant Factors Causing Delay and Cost Overruns in Construction of Groundwater Projects in Ghana

Abstract: In groundwater construction projects, many variables affect construction schedule and cost overruns. This paper aims to examine and evaluate the relative importance of the main factors that cause delay and cost overruns in groundwater construction projects. In order to identify these factors, a questionnaire survey was conducted. Questionnaires were sent to professionals involved in groundwater construction projects in Ghana. The data was analyzed and ranked, based on the profession of the respondents and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…This result agrees with Frimpong and Oluwoye (2003) who found that financial problems are the main factors that cause delay in the construction of groundwater projects in Ghana. Financial difficulties have also been identified as the first major factor causing delay in construction projects in Malaysia (Alaghbari et al 2007, Assaf et al 1995.…”
Section: Financialsupporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees with Frimpong and Oluwoye (2003) who found that financial problems are the main factors that cause delay in the construction of groundwater projects in Ghana. Financial difficulties have also been identified as the first major factor causing delay in construction projects in Malaysia (Alaghbari et al 2007, Assaf et al 1995.…”
Section: Financialsupporting
confidence: 92%
“…It is endemic and its economic and social impact is often discussed. However, studies on the causes could not be found in the published literature except the study by Frimpong and Oluwoye (2003) which investigated the significant factors that cause delay and cost overruns in the construction of underground projects in Ghana. They reported that to a large extent, consultants, owners, and contractors agreed that project financing, economic and natural conditions and material supply were the four major categories of causes of delay and cost overrun factors.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the survey results ( Al-Khalil and Al-Ghafl y, 1999 ;Frimpong and Oluwoye, 2003 ) show that fi nancial problem is one of the main causes of delays. Although the problem of delays looms large in the local construction industry, no attempt has been made to identify the root causes of fi nancial-related problems.…”
Section: Delays In Construction Projectsmentioning
confidence: 99%
“…Scholars have done a lot of research on the cause of this problem, pointing out that financial factor is one of the main reasons affecting the construction progress. Research has shown that financial factor is one of the main reasons for delays of engineering construction progress and cost overrun in Ghana [7]. In Thailand, survey and design, the contractor and the relevant factors of supervision are the important factors influencing the large engineering project delays, of which the lack of resources, such as the contractor's financial difficulties matters a lot [8].…”
Section: Literature Reviewmentioning
confidence: 99%